God en genot - J. H. van Wyk (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 1997)
It cannot be denied that the theology of Augustine in general and his ethics in particular have had an immense influence on theological scholarship, church practice and Christian life throughout the centuries. His use of especially the concepts uti and frui has had a great impact on Christian ethics. These concepts are generally understood in such a way that God must only be enjoyed (frui) for his own sake and everything else must be used (uti) (not enjoyed) for God's sake. The question, however, arises whether that is a correct interpretation of Augustine? Was he indeed more of a Neoplatonist and Stoicist than a Biblical theologian? In this article Augustine's use of these concepts as well as his influence on reformed ethics in this regard is investigated.